Analysis of protection system setting in 11KV distribution system / Ammar Alamshah - Ammar, Alamshah (2020)
One of the fundamental protections used in electrical network power system is Overcurrent and Earth Fault (OCEF) protection. They have to be both sensitive and quick in minimizing the electrodynamic and thermal stress imposed on the equipment during the fault time interval. It is utmost important for the relays to be capable of removing only the faulty section while keep up the flexibly to solid areas in the system. In order to achieve this objective, correct relay coordination setting is important to prevent the system from suffering catastrophic effects. These days, the consumer is enforcing raising performance demands by reducing operational and maintenance costs. At the same moment, improvement of the consistency and quality of supply is required. The cumulative fault current at each bus in the network needs to be determined to achieve the most effective relay coordination. This will be along with the calculation of relay settings to get the Time Setting Multiplier (TMS) value. The differential time graph of the relay grading curves will be plotted based on the value of size of CT, current setting, relay characteristic and TMS. This is due to the small margin inherited from the upper-stream utilities, a thorough analysis needs to be performed to achieve the strongest relay communication to a ring delivery network. This research report includes of reviewing of new ones of OCEF relay coordination setting in a ring distribution system, calculations on fault current, and suggestion on improvement of the relay coordination setting using directional relay and non-directional relay. A software to use for OCEF relay simulation of a distribution system was developed by writer using Microsoft Excel. It consists of fault current calculation, relay setting calculations and graphical plot of the relay grading curves. The proposed improvement of the relay coordination environment using directional relay and non-directional relay would provide a better method of distribution in terms of reliability and maintainability.